CHCI-Mellon Crises of Democracy Global Humanities Institute Curriculum - Ohlmeyer, Jane; Apor, Balazs; Cosgrove, Mary; Edmond, Jennifer (Consortium of Humanities Centers and Institutes, 2019)
The Crises of Democracy Global Humanities Institute (GHI) was an 18-month project (2018-19) funded by the Consortium of Humanities and Centres institutes and the A.W. Mellon Foundation. The GHI brought together a consortium of humanities scholars spanning four continents to explore various threats to democracy through the lens of cultural trauma from a comparative global perspective. The Trinity Long Room Hub Arts and Humanities Research Institute, Trinity College Dublin, led the GHI in partnership with the University of São Paulo, Jawaharlal Nehru University, University of Zagreb, and the SOF/Heyman Center at Columbia University. The Crises of Democracy Curriculum is a multimodal open-access learning material based on the programme of the GHI summer institute held in Dubrovnik in July 2019. The programme included lectures, panels, practical skills workshops, film screenings, and early career researcher presentations. The GHI faculty designed the curriculum: Balázs Apor, Nebojša Blanuša, Angela Butler, Rosemary Byrne, Arlene Clemesha, Mary Cosgrove, Eileen Gillooly, Jennifer Edmond, Esther Hamburger, Marianne Hirsch, Stephanie McCurry, Sucheta Mahajan, Aditya Mukherjee, Mridula Mukherjee, Jane Ohlmeyer, Tomislav Pletenac, Bodh Prakash, Urmimala Sarkar Munsi, and Bruce Shapiro.